Supporting dual career in Spain: Elite athletes' barriers to study. (November 2015) - López de Subijana, Cristina; Barriopedro, Maribel; Conde, Elena
Abstract: Objective: The aim of this study was to analyze whether a Career Assistance Program (PROAD) facilitates the dual career. Design and method: A cross-sectional, prospective and quantitative design was used. A questionnaire was sent to all of Spain's elite athletes from Olympic sports. Of the 2378 elite athletes, 575 (332 men and 243 women) completed the 29-item questionnaire. The overall response rate was 24.2%. Results: Most of the athletes perceived the dual career as difficult. Their most significant barriers are related to time management. The PROAD athletes and the non-PROAD athletes encountered the same barriers to studying. In general, the PROAD program seemed to have a positive effect on the academic level an athlete achieves. The athletes enrolled in the PROAD were more informed than the non-enrolled athletes. PROAD athletes were more proactive in demanding help and they had a closer relationship with the Spanish Sport Council than the non-PROAD athletes. Conclusions: Student-athletes have several problems with the normalized educational system. Sport psychologists should reinforce the athlete's strengths, and they should seek the opportunities the sport context provides to athletes. The barriers could be minimized by adopting certain strategies. The PROAD program seems to be useful in terms of providing information, in ensuring elite athletes work or study before the end of their sports career, in making them responsible and autonomous, and in being more active. Highlights: It's the first prospective research with a large sample of the Spanish elite athlete population. The dual career is perceived as difficult by elite athletes. The main barriers for studying have been identified. The PROAD seems to positively influence on the academic level of the elite athletes enrolled on the program.